Environmental Training Strategy For A Sustainable Human Development In The Medical Studies - Rodríguez Cabrera, Ileana; Vicedo Tomey, Agustín; Obregón Ballester, Gil (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: Universities confront the challenge to train professionals to face different problems, deterioration of the environment is one of them. Universities must promote the environmental training of professionals through the inclusion of the environmental dimension in the teaching process. In the case of health professionals this issue has a greater connotation due to the relationships between environmental problems and health problems. Objective: To propose a strategy on environmental training aimed at the sustainable human development in medical studies. Methods: Literature review on the topic was done and theoretical methods were used. Different definitions and varied structures were contrasted. Results: Structure of the proposed strategy including components and stages was designed. Conclusions: A strategy for environmental training aimed at the sustainable human development to introduce the environmental dimension in the medical studies is proposed.